Avaliação da atividade de compostos de guanidina, selenoglicolicamidas e espiro-acridínicos sobre leishmania infantum - Almeida, Fernanda Silva (2022)
Leishmaniasis is a neglected tropical infectious disease complex with thousands of cases annually; being of major global health concern, particularly the most severe form, visceral leishmaniasis. Treatments for visceral leishmaniasis are limited and have serious adverse effects. Compounds containing guanidine, selenium, and acridines have shown biological activities, including antiparasitic. Therefore, we analyzed the cytotoxic effects of these various compounds containing guanidine, acridine derivatives, and selenoglycolicamides on Leishmania infantum in their promastigote and amastigote forms in vitro, their cytotoxicity in human cells and their effects on the production of reactive nitrogen species. As for the activity of acridine derivatives, the IC50 values ranged from 1.10 to 6.05μg/mL for promastigote forms of Leishmania (Leishmania) infantum. In the activity under axenic amastigotes of the most active compounds, there is an expressive activity of AMTAC 11 (EC50= 0.97 ± 0.2 μg/mL) and low cytotoxicity in mononuclear cells of the peripheral system (CC50= > 100 μg/mL ). For the compounds of the selenoglycolicamides group, of the 9 compounds evaluated, 8 showed inhibitory activity against L. infantum promastigotes with IC50 ranging between 1.34 and 68.96 μg/mL. In terms of cytotoxic activity for amastigotes, the most promising compound, MSe 13, showed an EC50 of 14.59 ± 1.44 μg/mL. Within the concentrations tested, none of the compounds showed toxicity in human erythrocytes. To identify the mechanisms of action, the processes of cell death were evaluated by staining with annexin V and propidium iodide and nitrite production. As for the evaluation of the cell death profile, selenoglycolicamide MSe 13 induced cell death by apoptosis in axenic amastigotes, however, MSe 13 still induced a percentage of cell death in PBMC by apoptosis, as well as the reference drug Amphotericin B. LQOFG-2, LQOFG-6 and LQOFG-7 showed IC50 values between 5.14 and 10.76 μg/mL, respectively, in promastigotes. These compounds exhibited cytotoxicity on axenic amastigotes at values of 10.59; 8.15 and 8.46 μg/ml. The guanidine derivatives showed no apparent cytotoxicity in cells from healthy donors. Compounds containing guanidine showed a significant percentage of amastigotes to apoptosis. Regardless of L. infantum infection, LQOFG-7 increased nitrite production in PBMC's suggesting a potential mechanism of action for this compound. Therefore, these data suggest that guanidine derivatives, selenoglycolicamides, and spiro-acridines are potential molecules for anti-Leishmania activity, and more research is needed to fully understand their mechanism of action.